ABOUT DOMESTIC VIOLENCE AGAINST MINOR CHILDREN - VICTIMS OF VIOLENCE (Journal of actual problems of jurisprudence, 2024)
One of the important problems related to violation of children's rights is a violence against children and child abuse. Abuse and neglect of a child’s basic needs are any actions or inactions of parents, surrogate parents or other adults that impair the child’s health and well-being or create conditions that interfere with the child’s optimal physical or mental development, violate the child’s rights and freedom. Depending on the nature of the harm caused to the child, there are forms of abuse and types of violence. Many countries already have a certain methodology for identifying such cases, new methods are being developed and measures are being taken to combat domestic violence. In Kazakhstan, the legislative framework and system for identifying and combating domestic violence are not sufficiently developed. In order to increase the efficiency of efforts aimed at combating domestic violence, it is necessary to develop and implement a system for preventing and identifying cases of domestic violence, based on research, analysis and monitoring of incidents in our country, as well as on the experience of foreign countries in combating this phenomenon. Consequently, scientific research on domestic violence against children helps to identify the causes, mechanisms and factors that provoked such violence, which in turn contributes to the development of effective measures to protect children; understand the effects of domestic violence on the psychological and emotional health of children, which is important for the development of preventive and rehabilitation programs; influence public opinion the perception of domestic violence and can contribute to changing social norms and norms of current legislation in the direction of more effective protection of children; They play an important role in training social workers, educators, doctors and other professionals, allowing them to respond effectively to cases of violence and provide assistance to victims. The scientific article was prepared within the framework of program-targeted funding for scientific and (or) scientific and technical programs for 2023-2025, aimed at implementing the project IRN BR 27882414 “Program for the support and rehabilitation of child victims of violence: practical implementation of a network of modular resource centers”, financed by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan.         Key words: violence, minors, child, children, opposition, family, domestic.